(3HTGFQ Cgd GdGjeGf HaJhMGJ Bd YKeGfs - (3MSjf Hf Ydj Hf SdjeGf GdJhfSj GdMfaj, MSjf NhLg,J (B1169 (3g` s
(3ChdgG (B:s
(3gPG eG GSJNQLg ef dSGfi GdJQcjI hGdaGQSjI hJQLeI HGddZI GdYQHjI MSjf NhLg Hf Ydi GdMeO ddg GdPi TQY GdLgGO dYHGOg CeG HYO , adeG cGf GLgGO bGQYI JUjH GdcaGQ HeMGSf SdWfI edhc GdYGde s
(3BNQgG (B:s
(3Ke SQJ Edi RjGQI ebGe GdTjN GdCcHQ eMi GdOjf Hf YQHi Ke Efi ONdJ GdRGhjI HGdeOQSI ahLOJ GdTjN YHO GdZfi ajgG hRQfG HMeO Gddg GdeSLO GdCbUi hGdUNQI GdeHGQcI hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3GHJOC GdeDda ai JYQjHI hLeYg SfI (B1136(3g` hCJeg ai YGe (B1137(3g`s
(3HBNQgG Hbde fSN eNJda CfgG fbdJ ef fSNI cJHJ ai BNQgG HNW GdeDda Cfg WGdYgG hbGHdgG Ydi GdCUd ef ChdgG Edi BNQgG aCUdMgG hUMMgG hPdc SfI (B1142(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B248 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B625s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B182 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B687 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
Keywords: (3GdJGQjNs